Influencia de los programas sociales en el estado nutricional de los niños y niñas de 12 a 36 meses, San Pablo Cajamarca 2012. - Tello Correa, Gladys Marleny (2014)
Malnutrition has become a very important social problem level of all regions of the world, implementing several policies to address them. This research has aims to determine the influence of social programs: glass milk program, integral nutrition program and Juntos program in the nutritional status of the children from 12 to 36 months, District San Pablo- Cajamarca. The study is quantitative, design correlational and cross-sectional; was performed in 115 children. It came to the following conclusions: the nutritional status of the children was: 53% with chronic malnutrition, 31.3% with normal nutritional status and 14.8% with global malnutrition. Of the children that benefited of a social program (11.3%), 5.2% had normal nutritional status and 5.2% chronic malnutrition; those that received two social programs (27.8%), 19.1% had chronic malnutrition and of the children that benefited of three social programs (60.9%) also predominated the chronic malnutrition with 28.7%. Of the children that benefited of the glass milk program, for the period of 1 to 2 years (28.7%), 19.1% had chronic malnutrition, in the case of the integral nutrition program 48.7% also benefited by a period of 1 to 2 years of them 29.6% had chronic malnutrition; in the Juntos program 14.8% of children with chronic malnutrition that benefited for a period of 2 to 3 years (32.2%). The children that benefit of the social programs monthly, mostly had chronic malnutrition: glass milk program (25.2%), integral nutrition program (53%) and in the program Juntos (32.2%). No significant relation was found for social programs: Glass of milk, integral nutrition program and Juntos program, in the nutritional status of the children 12 to 36 months.